TCF4 (E2-2) harbors tumor suppressive functions in SHH medulloblastoma - Hellwig, Malte; Lauffer, Marlen C.; Bockmayr, Michael; Spohn, Michael; Merk, Daniel J.; Harrison, Luke; Ahlfeld, Julia; Kitowski, Annabel; Neumann, Julia E.; Ohli, Jasmin; Holdhof, Doerthe; Niesen, Judith; et al. (Acta Neuropathologica, 2019)
The TCF4 gene encodes for the basic helix-loop-helix transcription factor 4 (TCF4), which plays an important role in the development of the central nervous system (CNS). Haploinsufficiency of TCF4 was found to cause Pitt-Hopkins syndrome (PTHS), a severe neurodevelopmental disorder. Recently, the screening of a large cohort of medulloblastoma (MB), a highly aggressive embryonal brain tumor, revealed almost 20% of adult patients with MB of the Sonic hedgehog (SHH) subtype carrying somatic TCF4 mutations. Interestingly, many of these mutations have previously been detected as germline mutations in patients with PTHS. We show here that overexpression of wild-type TCF4 in vitro significantly suppresses cell proliferation in MB cells, whereas mutant TCF4 proteins do not to the same extent. Furthermore, RNA sequencing revealed significant upregulation of multiple well-known tumor suppressors upon expression of wild-type TCF4. In vivo, a prenatal knockout of Tcf4 in mice caused a significant increase in apoptosis accompanied by a decreased proliferation and failed migration of cerebellar granule neuron precursor cells (CGNP), which are thought to be the cells of origin for SHH MB. In contrast, postnatal in vitro and in vivo knockouts of Tcf4 with and without an additional constitutive activation of the SHH pathway led to significantly increased proliferation of CGNP or MB cells. Finally, publicly available data from human MB show that relatively low expression levels of TCF4 significantly correlate with a worse clinical outcome. These results not only point to time-specific roles of Tcf4 during cerebellar development but also suggest a functional linkage between TCF4 mutations and the formation of SHH MB, proposing that TCF4 acts as a tumor suppressor during postnatal stages of cerebellar development.
CRIS-Team WoS Importer:2019-04-04